THE CULTURE OF ARABIC LANGUAGE LEARNING IN THE PERSPECTIVE OF BERNARD SPOLSKY'S LANGUAGE POLICY - Ridwan, Ridwan; Yaqin, Muhammad Ainul; Saudin, Budi Marta; Bin Ahmed, Amar Bin Muhammad (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
This article examines the culture of Arabic language learning through the perspective of Bernard Spolsky's language policy. Spolsky defines language policy as language practice, language belief, and language management. In the context of Arabic language learning, language policy includes the implementation of appropriate curricula, effective teaching methods, and sustainable management of education. This research uses qualitative studies. Data collection techniques are carried out through observation, interviews and documentation. To perform data analysis, researchers use analytical theory according to Miles and Hiberman by condensing data, presenting data and drawing conclusions. At the data validity checking stage, researchers used triangulation methods and peer discussions.The study's findings are as follows: First, the ministry of religion's policy teaching materials are implemented using the minister of religious affairs' decree number 183 of 2019, and the administration of both madrasas construct learning plans, selecting appropriate learning media and methods. In madrasah Aliyah Negeri 2 Malang, the concept is similar. In developing learning activities, there involves planning for learning. Second, in both madrasas, the actuality of studying Arabic is based on the 2013 curriculum. And the ministry of religion's policy in the field to be more innovative and intensive on learning Arabic, as well as the idea of dimadrasah Aliyah negeri 2 Malang for arabic language learning to be done in a network or from home.